Auditory and Vestibular Side Effects of FDA-Approved Drugs for Diabetes - DiSogra, Robert M.; Meece, Jerry (Seminars in Hearing, 2019)
As of September 10, 2019, there were 75 medications (oral/injectable/inhalants) approved by the U.S. Food and Drug Administration for diabetes management: 1 inhalant, 21 oral combinations, 22 injectable, and 31 oral medications (not in combination with any other diabetes drug). This article isolates the auditory and vestibular side effects of those drugs as reported by the drug's manufacturer as well as those side effects that could interfere with a balance assessment. Twenty of the 75 approved medications (26%) could have an auditory-related side effect. Hearing loss and tinnitus are not on the list. Only two, or just 3%, have vertigo and spinning as reported side effects (one each). More than 50% of the drugs will have some effect on a balance assessment. Audiologists who evaluate a patient with diabetes (PWD) are presented with symptoms that could be related to their diabetes medication. Although the manufacturer might report a side effect as rare or as a percentage from their clinical trials subjects, not all PWD will experience these adverse events. Auditory and vestibular side effects do not dominate the diabetes drug side effect list, but, rather, the most reported side effects could impact a balance assessment. The lists that appear in Appendices A and B should serve as a guide for all professionals involved in managing the PWD (i.e., audiologists, otolaryngologists, diabetes educators, pharmacists, optometrists, dentists, etc.). The list also serves as a counseling tool if a communication problem emerges during the progression of the diabetes.
Keywords: adverse reaction; side effect; U.S. Food and Drug Administration; type 1 diabetes; type 2 diabetes